Energy from Crops: Production and Management of Biomass/Energy Crops on Phosphatic Clay in Central Florida - J. A. Stricker; Gordon M. Prine; D. L. Anderson; D. B. Shibles; T. C. Riddle (EDIS)
While it appears that biomass/energy crops may be successfully grown on phosphatic clay soils, a processing facility is needed to convert the biomass to energy in the form of methane, ethanol or electricity. Without an appropriate facility, there is no market for the crop. This document is Circular 1084, a publication of the Agronomy Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: February 1993. Revised: September 2003.